Integration of Information Technology into the Operational System of Cooperatives (Case Study of KPSBU LEMBANG) - Riyanto, Agus; Alailla, Ana; Mulik, Foland Tiara; Yuseliana, Rika; Mochamad Mir’an Kholid (Universitas Komputer Indonesia, 2025)
In today's digital age, cooperatives face various operational challenges stemming from limited resources, both financial and non-financial. This situation necessitates strategic innovation, one of which is through the integration of information technology into cooperative operational systems. This study aims to analyze how the application of information technology can support efficiency, transparency, and competitiveness at the Bandung Utara Cattle Farmers Cooperative (KPSBU) Lembang, one of the established cooperatives in West Java. The research method employs a qualitative approach in the form of a case study, with data collected through observation, in-depth interviews, and documentation. The research findings indicate that KPSBU Lembang has been implementing information technology since 2008, including digital systems for financial record-keeping, membership management, product distribution, and a GPS-based livestock census application. The use of these systems has proven to enhance work efficiency, data accuracy, and communication ease among members and management. However, the main challenges faced include limited digital literacy among older members and technical barriers such as poor internet signal in remote areas. KPSBU has responded to these challenges by providing regular training and manual solutions as alternatives. This study concludes that the integration of information technology has a positive impact on cooperative performance, with the caveat that infrastructure and human resource empowerment strategies need to be strengthened.